2020
DOI: 10.1111/padm.12649
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and legitimacy in collaborative public management: Mapping inter‐local agreements in England using social network analysis

Abstract: English councils have long aspired to be ‘self‐sufficient’, providing services within single jurisdictions with limited inter‐local collaboration. However, by 2017 almost all local councils (97 per cent) participated in one or more frontline or back‐office ‘shared service’ involving 338 distinct partnerships. We analyse this new‐found enthusiasm for inter‐council collaboration by performing exploratory social network analysis on organizational and financial data for all 353 English councils. We examine factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 84 publications
(113 reference statements)
0
14
0
Order By: Relevance
“…De Borger and Kerstens 1996). Second, administrative intensity is measured as the percentage of each district council's overall expenditure that is spent on central administrative services (see Dixon and Elston 2020). Third, we measure expenditure reductions as the annual percentage change in total expenditure per capita for each council (for a similar approach see Jordan 2003).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…De Borger and Kerstens 1996). Second, administrative intensity is measured as the percentage of each district council's overall expenditure that is spent on central administrative services (see Dixon and Elston 2020). Third, we measure expenditure reductions as the annual percentage change in total expenditure per capita for each council (for a similar approach see Jordan 2003).…”
Section: Methodsmentioning
confidence: 99%
“…To analyze the political factors shaping adoption of a shared SMT, right‐wing party rule is measured using a dichotomous variable coded 1 for councils controlled by the Conservative Party and 0 otherwise (see Dixon and Elston 2020). Next, electoral competition is measured by calculating the percentage difference of the share of the vote gained by the two parties winning the most votes in the most recent local election subtracted from 100 (see Pattie and Johnston 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars have observed that the affluence of a community often drives its priorities, may facilitate and/or constrain the ability of localities to offer services, and affects the willingness/ability of local policymakers to engage in innovation (Dixon and Elston 2020). Hajnal and Trounstine (2010), for example, concluded that cities in poor fiscal health are limited in what services they offer as well as how they distribute resources.…”
Section: Literature and Backgroundmentioning
confidence: 99%